“A CONCISE OUTLINE OF THE 5-POINTER ANTOA COUNTDOWN” BY RALF G WILL = RGW23C - Will, Ralf G (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Aim of this article is a concise overview of ANTOA from Point 1 to 5. It is also a comprehensive selection of comments and annotations to the various benchmarks that form an unusual perimeter, encircling the social context of creative expression.While Point 1 looks for individual footprint and intrinsic character, Point 2 deals with environmental concern and how Art builds social relations viceversa becomes tool for conscientising communal dissent.Point 3 explains the old-meets-new condition whereby relevant Art supports sensible skill upheaval and innovative presentation. Trendy convention changes to refreshing renewal of mindful invention.Point 4 is pure nature, the abstraction of once relevant and definite objects, impressing edgy sentiments on keen consumers and practitioners alike. Often misunderstood as child play, the abstraction needs to have a beginning and an end, and may not contain meaning. Even though it satisfies curiosity and owns an excessively provocative price tag. Point 5 illustrates value, meaning and symbol, and returns to memory and experience as creators of history.The social construction of Art calls for meaning and value and tightens the net of inter-human relations, no matter in the stone age or the controversial period termed modernity or contemporary Art. Meaning has indeed come from social acceptance of the creative flow, the free spirit that paradoxically works best in scientific way, endowing Art with a certain dialect of symbolic language. Weaving individual relations into a social fabric of communal meaning.